KESALAHAN SISWA MTS DALAM MEMAHAMI SOAL TES PADA MATERI HIMPUNAN BERDASARKAN TAKSONOMI BLOOM LEVEL KOGNITIF - Suci Nur Harisma; Nelly Fitriani; Puji Nurfauziah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of the research is to identify errors experienced by students in answering or solving questions in the set material. This research was conducted using a qualitative descriptive method with the subject of the study, namely 23 class VII students in Bandung for the 2022-2023 academic year. Data collection is carried out through the provision of mathematical problem tests on set materials. The data analysis technique used in this study conducted an assessment of students' answers, determined the wrong answers on the student's answer sheet and calculated the percentage of errors. The results showed that the highest indicator had an error, namely the indicator of solving contextual problems in the set material with a percentage reaching 70.91%. The factors that cause errors in solving set questions are due to students' lack of understanding in defining the set, stating the set by registering its members as a set, stating the relationship between the association and the venn diagram, low students in the ability to solve story problems and lack of accuracy of students when doing questions.